The mystery of glaucoma - Czechowicz-Janicka, Krystyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
The concept of glaucoma approach as to disease secondary to certain morphological changes – of origin not yet completely clarified. This paper was presented in the Symposium Opening Ceremony lecture. It seems, that in the future, we should expect some gene therapy alternatives to the treatment algorithms applied in therapy of glaucoma, nowadays.